'It Depends': A qualitative study on how adolescent students explain bystander intervention and non-intervention in bullying situations. (August 2018) - Thornberg, Robert; Landgren, Lena; Wiman, Erika
The aim of the current study was to examine how junior high school students interpret, motivate, and explain various bystander behaviors in bullying situations. The participants were 17 junior high school students recruited from four schools in Sweden. Semi-structured interviews were conducted and analysed with grounded theory methods. The analysis generated a conceptual model of bystander interpreting–considering process in school bullying. A core category named 'it depends' was developed to explain how the participants in the study motivated their own and their peers' actions as bystanders in various bullying situations. Whether they intervened or not depended on how they interpreted the situation in terms of: (a) seriousness of the situation, including trivialization; (b) social relationships with the involved; (c) locus of responsibility, including displacement of responsibility, and victim blame; (d) social status; (e) perception of risk; and (f) defender self-efficacy. The implications of these results for bullying prevention and intervention efforts are discussed.